2015
DOI: 10.1111/ijd.13064
|View full text |Cite
|
Sign up to set email alerts
|

Mysterious chronic urticaria caused by Blastocystis spp.?

Abstract: Species of the genus Blastocystis, which are single-cell, intestinal protozoan parasites of humans and animals, remain mysterious, with unclear clinical and epidemiologic significance. In recent years, many researchers have suggested a possible connection between Blastocystis spp. infection and chronic urticaria. In the present article, we review the literature and discuss the possible associations between the clinical symptomatology and pathogenicity of this organism in terms of its subtypes, morphologic form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 66 publications
0
32
0
11
Order By: Relevance
“…However, this limitation would not apply to helminths, for which the diagnostic approach used in the present study has been assessed several times and has shown high sensitivity and specificity [17, 23, 24, 29]. Nor would it apply to urticaria, which is commonly associated with other helminths including Ascaris lumbricoides , Hymenolepis nana , and Fasciola hepatica , as well as with protozoans including Giardia lamblia and Blastocystis hominis [28, 30, 33, 49, 50]. While we cannot exclude that some protozoan infections were missed, ivermectin is not effective against G .…”
Section: Discussionmentioning
confidence: 99%
“…However, this limitation would not apply to helminths, for which the diagnostic approach used in the present study has been assessed several times and has shown high sensitivity and specificity [17, 23, 24, 29]. Nor would it apply to urticaria, which is commonly associated with other helminths including Ascaris lumbricoides , Hymenolepis nana , and Fasciola hepatica , as well as with protozoans including Giardia lamblia and Blastocystis hominis [28, 30, 33, 49, 50]. While we cannot exclude that some protozoan infections were missed, ivermectin is not effective against G .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic data by Denoeud et al [38] combined with in-vitro and in-vivo studies of Wu et al [39] and Ajjampur et al [28] allowed the identification of recognized virulence factors and revealed the harmful influences of the parasite on the intestinal barrier, leading to credible models of pathogenesis [40]. Several papers also suggest that this parasite should be related with non-specific gastrointestinal symptoms like diarrhoea, abdominal pain, and vomiting, and additionally, an association between B. hominis and irritable bowel syndrome (IBS) [40] and urticarial [41] is suggested.…”
Section: Pathogenicity Of Blastocystis Sp Is a Relationship Possiblementioning
confidence: 99%
“…colonization was shown to be associated with increased diversity of human gut bacterial microbiota [14], suggesting that the parasite requires high overall microbial diversity to become established in the human colon [3]. Much current data also suggests that this parasite should be associated with non-specific gastrointestinal symptoms including diarrhea, abdominal pain, and vomiting [1], and is suspected to be linked to irritable bowel syndrome [13] and urticaria [15]. …”
Section: Introductionmentioning
confidence: 99%